Risk factors of complicated respiratory tract infection inimmunosuppressive therapy of primary nephrotic syndrome - LIU Kun; YANG Jin-jin; LI Sheng-kai (Linchuang shenzangbing zazhi)
Objective To investigate the clinical features and risk factors of complicated respiratory tract infection of primary nephrotic syndrome(PNS). Methods From January 2015 to July 2017, 203 patients with PNS in the nephrology department of our hospital were selected, among whom 156 ones(76.8%) were complicated with respiratory tract infection, 105 ones(51.7%) with upper respiratory tract infection, and 51 ones(25.1%) with lower respiratory tract infection. The clinical characteristics and risk factors were retrospectively analyzed. Results During immunotherapy, the incidence of upper respiratory tract infection in PNS patientswas 18.2% ～ 24.1%, and the incidence of lower respiratory tract infection reached the highest value of 6.1% in the second month.There were no significant differences in renal pathological types between the groups.The patients with lower respiratory tract infection, their ages had greater age, faster heart beat, higher singly daily hormone dose,lower lymphocyte count, monocyte count, hemoglobin, serum albumin, Immunoglobulin G(IgG) andestimated glomerular filtration rate(eGFR) level, and higher urea, creatinine, urinary immunoglobulin G, c-reactive protein(CRP), lactate dehydrogenase(LDH).Low immunoglobulin G, lymphocyte, albumin levels, and hormone combined immunosuppressant use were independent risk factors for lower respiratory tract infection. Conclusions In the pathological progression of PNS patients, the incidence of upper respiratory tract infection is higher, and the incidence of lower respiratory tract infection is the highest in the second month of immunotherapy. Patients with low immunoglobulin G, low lymphocyte and albumin levels, combined with hormone and immunosuppressive drugs, are prone to lower respiratory tract infection.